A High-Performance Routing Protocol Based on Mobile Agent for Mobile Ad Hoc Networks - Quy, Vu Khanh; Chuan, Pham Minh; Nam, Vi Hoai; Linh, Dao Manh; Ban, Nguyen Tien; Han, Nguyen Dinh (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This paper presents a modification of a well-known routing protocol, namely Ad hoc On-Demand Distance Vector, as a solution to improve the performance of mobile ad hoc networks. We adapted the mobile agent technology as to novel metrics for routing in those networks. The metric is a function of the loss rate, the bandwidth and the end-to-end delay of the link. Indeed, we established a new tunable parameter to obtain a tradeoff between throughput and delay when computing the new metric. As a result, any routing protocol using this metric can al-ways choose a high-throughput and low-delay path between a source and a destination. Hence, the achievable performance of the mobile ad hoc networks has been improved remarkably with our modified routing protocol,